The Influence of Desiccation Level of Preservation Aloe Vera - Doddy Irawan (Suara Teknik : Jurnal Ilmiah, 2010)
Aloe Gel a contained in the leaves, colerless with 99.5% of water content and0.5% solid content. This high water content empowers the chemical reaction andsome microorganism activities to take place. Therefore, we loaked into some praticalprocess so that the Aloe Gel can stay fresh longer. The efforts were concentrated onthe drying process of the leaves. A too high drying temperature will damage the gelcomponents, so the right temperature should be found to minimize the damages.A lab built cabinet dryer was used for convenient control of temperature andeasy air circulation control and timing to preserve the good nutrition and texturecharacteristics. The optimal combination of drying time and temperature was theexpected result of our research.Five time periods were selected, which one 10, 15, 20, 25, and 30 minutes,with varying temperatures. We found out that the best time was between 25 and 30minutes and temperatures between 700 and 800C. The resulting water contentsbetween 97 and 99.5%, while the consumers gave the grade 4, which meant good forthe dried gel.Keywords : Drying ,Cabinet Dryer, Preservation